Coronavirus disease-19 vaccine development utilizing promising technology. Issue 6 (November 2020) - Wang, Yihan; Xing, Man; Zhou, Dongming
Abstract : Purpose of review: Coronavirus disease-19 (COVID-19) is a highly transmittable and pathogenic pneumonia-causing disease, which is caused by severe acute respiratory syndrome coronavirus-2, resulting in millions of deaths globally. Severe acute respiratory syndrome coronavirus-2 may coexist with human populations for a long time. Therefore, high-effective COVID-19 vaccines are an urgent need. Recent findings: Vaccines help in the development of long-lasting humoral or cellular immunity, or both, by exposing individuals to antigens that induce an immunological response and memory prior to infections with live pathogens. New vaccine technologies, such as viral vectors and nucleic acid-based vaccines, which represent highly versatile technologies, may allow for faster vaccine manufacture and scale up production. Summary: We summarized the recent progress made in relation to COVID-19 vaccine development using several promising technologies, with particular emphasis on advancements that are currently at the clinical trial stage.